Consulting report – Club Regatas Lima – optimization of invoicing management - Ashcallay Samaniego, Gabriela Guadalupe (2018)
Regatas Lima Club is a sports and recreational club that was founded in 1875. It is the oldest and largest club in Peru. After more than 100 years of existence, it has diversified into more than 40 different disciplines that members can practice. Regatas Lima Club started in Chorrillos where its headquarters is located, nonetheless, it did not stop growing and currently operates 5 more subsidiaries, distributed along Lima and other provinces of Peru. Regatas Lima Club is defined as a not-for-profit organization because its major goal is to provide members with high-quality sports facilities and availability of services. For this reason, the organization has to acquire different kinds of equipment and infrastructure for each special discipline. As a consequence, the Club has to work with high numbers of suppliers in order to maintain its reputation. Therefore, the problem identified through an internal and external analysis was the invoicing management inefficiency in the Department of Finance and Accounting, which controls all invoices of the whole organization. The consulting process focused on proposing short-term and long-term solutions for Regatas Lima Club, based on the qualitative and quantitative analysis. After assessing the alternatives through a cost and benefit analysis, a final solution is suggested. This proposal includes five principal components in order to optimize the invoicing management in the Finance and Accounting department, which are: specified delivery time, external invoicing only, invoicing excellence, lean processing, and training & clear instructions/workshops. Some additional components are defined and should be considered for a long-term strategy. The implementation plan is designed, taking into consideration, the organization’s time availability, human and material resources, in order to achieve a successful performance.